Nanoparticle effects on post-buckling behaviour of patched hybrid composites - Erdem, Serkan; Gur, Mustafa; Kaman, Mete Onur (Walter de Gruyter Gmbh, 2023)
In this study, the effect of particle additive on buckling behaviour in laminated hybrid composite plates was investigated numerically and experimentally for patched samples. In the experimental study, carbon-aramid woven fabric was chosen as the hybrid material and composite plate production was carried out in a temperature-controlled vacuum infusion production unit. The circular holed specimens were patched on one face with the wet patch and the adhesion performance under buckling load was investigated. The buckling test results for composite plates with and without nanoparticle added to patch matrix material were compared. In numerical study, the buckling analysis of composite plates patched with nano-additive and without nano-additive wet patch method was performed with the finite element method. The numerical results obtained in the nonlinear buckling analysis for plates and the experimental results were compatible with each other. Addition of 1 wt% carbon nano tube (CNT) and graphene to the patch material with fiber angle parallel to the loading direction increased the damage loads by 22.5 and 12.6 wt%, respectively, compared to the non-additive patch. Adding 2 wt% CNT increased damage loads by 50%, while adding 2 wt% graphene reduced damage loads only 1%.
Keywords: carbon nanotube; graphene; laminated composites; post-buckling; repair